Mortality due to COVID-19 in the regions of Peru regions of Peru between the frst and ffth pandemic waves - Fabian-Moya, Sthefani Paola (2023)
Objective. To determine mortality due to COVID-19 in the regions of Peru between the first and fifth pandemic waves. Methods. The research was analytical, observational, retrospective and cross-sectional. The data were obtained from the National Open Data Platform of the Ministry of Health (MINSA) and the National Information System of Deaths (SINADEF) and imported in Microsoft Excel format into the SPSS v.25 statistical program. The following variables were considered for the data collection form: age, sex, diagnostic criteria and regions. The KruskalWallis and Mann-Whitney nonparametric tests were used for statistical analysis. Results. A total of 218,770 deaths were reported during the period 2020-2022, with a mortality rate (MMR) of 744.6 x 100,000 inhabitants; 44.1% belonged to the department of Lima, mostly older adults of male sex. The  concentration according to macro-region was mainly in Lima with a MT of 1,022 x 100,000 inhabitants, and the north with a MT of 634 x 100,000 inhabitants. On the other hand, the virological diagnostic criterion was 37.7%, followed by SINADEF with 30.3%. Likewise, significant differences are shown in the ranges of the variables with a p < 0.05 (0.000). Conclusions. Mortality due to COVID-19 in Peru was high, with a mortality rate of 744.6 x 100,000 inhabitants, regardless of sex, age, region and diagnostic criteria; leading the Department of Lima.